Size : how it explains the world - Smil, Vaclav (William Morrow, an imprint of HarperCollinsPublishers, 2023)
What makes a human society too big? What about a human being? Which alternative energy sources have the best chance of scaling and reducing our dependence on fossil fuels? Why do tall people make more money? What makes a face beautiful? How about a cathedral? How can changing the size of your plates help you lose weight?